Level of Knowledge about Menstruation and Anxiety in Facing Menarche - Mustika Sari, Surya; Vidia Effendy, Henny (Universitas Islam Lamongan, 2025)
Menarche is one of the important phases in puberty experienced by girls. Lack of knowledge about menstruation often causes anxiety, fear, and unpreparedness in facing menarche. Sufficient knowledge from an early age plays an important role in shaping the mental preparedness of adolescents. This study aims to determine the relationship between the level of knowledge about menstruation and anxiety in facing menarche among fifth and sixth grade students at SDN Gayaman Elementary School in Mojoanyar District, Mojokerto Regency. This study used a quantitative approach with a correlational descriptive design. A total of 21 respondents were selected using total sampling technique. The research instruments were a knowledge questionnaire and an anxiety questionnaire regarding facing menarche. Data analysis used Spearman's rho correlation test to determine the relationship between the two variables. Most respondents had a good level of knowledge (61.9%) and experienced mild anxiety (61.9%). The results of the Spearman's rho test showed a p-value of 0.000 (< 0.05) and a correlation coefficient of 0.767, indicating a strong relationship between the level of knowledge about menstruation and the level of anxiety in facing menarche.